Analisis Faktor-Faktor Penyebab Kejadian Misfile di Puskesmas Kademangan Kabupaten Bondowoso - Desi Syahbaniar; Rossalina Adi Wijayanti; Feby Erawantini; Efri Tri Ardianto (Politeknik Negeri Jember, 2021)
The observation results of the medical record filing unit in Kademangan Public Health Service Bondowosofound that, in a week, 51 of 366 outpatient medical records were on the wrong location or lost (misfile) Theimpact of misfiling is the delay of service patients in search of medical records, duplication of numbersrecord the medical, and the contents of medical records document become not sustainable. This studyaimed to analyze the factors that cause medical records misfile in Kademangan Public Health ServiceBondowoso. This study used qualitative methods and data obtained through an interview, observation, andUSG (Urgency, Seriousness, Growth) method. The results of the research showed that the priority problemof misfile’s causes was the less of leadership motivation such as reward and punishment. The alternativesolutions were giving punishment or reward to medical record officers, especially to the filling officer tocreate their discipline in doing their work. The discipline of the filing officers in conducting work makes themanagement of filing medical records run optimally